Family Adjustment When Facing Pediatric Cancer: The Role of Parental Psychological Flexibility, Dyadic Coping, and Network Support - Van Schoors, Marieke; De Paepe, Annick Lena; Lemiere, Jurgen; Morez, Ann; Norga, Koenraad; Lambrecht, Karolien; Goubert, Liesbet; Verhofstadt, Lesley L. (Frontiers in Psychology, 2019)
Objectives Pediatric cancer is a life-threatening disease that poses significant challenges to the life of all family members (diagnosed child, parents, and siblings) and the family as a whole. To date, limited research has investigated family adjustment when facing pediatric cancer. The aim of the current study was to explore the role of protective factors at the individual (parental psychological flexibility), intrafamilial (dyadic coping) and contextual level (network support) in explaining family adjustment as perceived by parents of children with leukemia or non-Hodgkin lymphoma. In addition, we were interested to see whether these protective factors could be predictive for family adjustment at a later time point. Method Participants were 70 mothers and 53 fathers (80 families) of children with leukemia or non-Hodgkin lymphoma. Mean time since diagnosis was 5.26 (T1) and 18.86 (T2) months post-diagnosis. Parents completed the Acceptance and Action Questionnaire II (to assess psychological flexibility), Dyadic Coping Inventory, a network support questionnaire, Impact on Family Scale and the Family Adjustment Scale. Both concurrent and prospective association models were tested. Results Psychological flexibility, dyadic coping and network support proved to be cross-sectionally and positively related to parents’ perception of family adjustment post-diagnosis; psychological flexibility and dyadic coping proved to predict better family adjustment over time. Conclusion Our findings led to the conclusion that protective factors at all three levels (individual, intrafamilial and contextual) are important for explaining family adjustment as perceived by parents facing a diagnosis of cancer in their child. Interventions targeting the individual, couple, as well as family level are warranted to enhance family adjustment.